Dramatización con enfoque lúdico y su contribución en la expresión corporal a los estudiantes de la Escuela de Educación Básica Mariscal Sucre parroquia Zapotal, cantón Ventanas, provincia los Ríos - Rodríguez Tapia, Tania Mercedes (2018)
I have considered focusing on the importance of music, dance, dramatization and storytelling as a way of expression for children in Early Childhood Education, and as a method to help the development of imagination, creativity, socialization, affectivity, etc. Leaving them free for the free expression of emotions. I think it is a job that will help teachers to focus on body expression in a playful way, so that children are able to learn while having fun. I intend to establish what is and how you can work on the corporal expression as proposed by the authors that I have consulted taking into account the four aspects on which I have based, making it clear that the corporal expression is necessary to work from an early age granting in this way, the same importance we give to reading and writing in the educational field. The importance of all this lies in the benefits that this type of expressions has in the learning process of the child, and what I intend in this work is to show how, through various activities of corporal expression, children establish the first foundations for a optimal development.